2004
DOI: 10.1016/j.ijgo.2004.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Management of the third stage of labor in an Egyptian teaching hospital

Abstract: Objectives-The study describes normal labor practices in an Egyptian teaching hospital for the first time, where postpartum hemorrhage is the leading cause of maternal mortality. Third-stage management patterns are described and compared to evidence-based medicine. Reasons for thirdstage practices observed are explored.Study design-176 normal births were directly observed. Women were interviewed postpartum and study findings were shared with providers.Results-Third-stage active management was correctly done fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 11 publications
2
17
0
1
Order By: Relevance
“…This study's findings about the quality of management of the third stage of labor, particularly during the pre-intervention phase, are in agreement with what was found by Cherine et al [25]. Day-to-day practice in delivery rooms can be inconsistent, especially when uterotonics are used.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study's findings about the quality of management of the third stage of labor, particularly during the pre-intervention phase, are in agreement with what was found by Cherine et al [25]. Day-to-day practice in delivery rooms can be inconsistent, especially when uterotonics are used.…”
Section: Discussionsupporting
confidence: 91%
“…A careful analysis of the management of the third stage of labor in an Egyptian teaching hospital showed that only 15% of the women received adequate AMTSL during the study period [25]. Staff shortages were given as the main explanation for the generally inappropriate management of deliveries, and that study's findings are not unique.…”
Section: Introductionmentioning
confidence: 84%
“…This paper presents selected findings from four studies documenting routine obstetric practices in Egypt, Lebanon, Syria and the West Bank and compares these to evidence‐based best practice. Other findings are presented elsewhere 16–20 …”
Section: Introductionmentioning
confidence: 66%
“…Observations were done by non‐staff female obstetricians using a 200‐item checklist covering 537 variables after obtaining informed consent. One woman refused to be observed 17,22 . Ward practices were also recorded and mothers were interviewed postpartum.…”
Section: Methodsmentioning
confidence: 99%
“…In one Egyptian hospital, third stage management practices were observed and it was found that third stage active management was correctly done in 15% of women observed. 12 In one WHO's facility based study of AMTSL in six countries where labour practices were directly observed in the third stage, it was reported that 94% of the women observed were given oxytocin or another uterotonic. There was variation between the countries in the practices CCT, uterine massage and timing of uterotonic administration.…”
Section: Resultsmentioning
confidence: 99%